2002
DOI: 10.26719/2002.8.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Red cell glucose-6-phosphate dehydrogenase phenotypes in Iraq

Abstract: We attempted to characterize biochemically glucose-6-phosphate dehydrogenase [G6PD] variants in Iraqi individuals. Thus 758 healthy Iraqi males aged 18-60 years were randomly selected and 46 [6.1%] were G6PD deficient. Although the predominant non-deficient G6PD phenotype was G6PD B [92.6%], G6PD A+ was found in polymorphic frequency [1.3%]. In the deficient group, 31 cases were fully characterized, including 17 cases with features consistent with G6PD Mediterranean variant, while 12 had other biochemical feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The majority of the cases were G6PD deficiency (6.7% of neonates examined), which is common in many Eastern Mediterranean nations, including Iraq (25)(26)(27). The incidence of G6PD deficiency in central and southern Iraq has been the subject of some investigations (28)(29)(30). Due to the COVID-19 outbreak, there were more infants examined in 2021 than there were in 2019 and 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the cases were G6PD deficiency (6.7% of neonates examined), which is common in many Eastern Mediterranean nations, including Iraq (25)(26)(27). The incidence of G6PD deficiency in central and southern Iraq has been the subject of some investigations (28)(29)(30). Due to the COVID-19 outbreak, there were more infants examined in 2021 than there were in 2019 and 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Almost a decade later Al-Hamamy and Saeed (1981), reported a higher overall frequency of 12.4% (13) . In the last few years however ,well organized studies reported frequencies of this deficiency in Baghdad (central Iraq), Basrah (southern Iraq) , Sulymania (Northern Iraq) and Arbil (Northern Iraq) (14,15,16) . The study from Baghdad was performed on male blood donors who were resident of the city Baghdad and revealed a frequency of 6.1% (14) ,while that from Basrah performed on premarital couples revealed the highest ever reported figure from the country at 15.3% (15) , the figures from Sulymania and Arbil, regions revealed a prevalence of 6.0% ,8.6% respectively (16) .…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years however ,well organized studies reported frequencies of this deficiency in Baghdad (central Iraq), Basrah (southern Iraq) , Sulymania (Northern Iraq) and Arbil (Northern Iraq) (14,15,16) . The study from Baghdad was performed on male blood donors who were resident of the city Baghdad and revealed a frequency of 6.1% (14) ,while that from Basrah performed on premarital couples revealed the highest ever reported figure from the country at 15.3% (15) , the figures from Sulymania and Arbil, regions revealed a prevalence of 6.0% ,8.6% respectively (16) . Despite the high frequency of this disorder in Iraq, and the large numbers of cases presenting in acute hemolytic episodes as a result, particularly in the spring (the fava bean season), or as neonatal jaundice , no study has ever focused on to determine the incidence of G6PD deficiency in Ninava governorate, the current study is the first to tackle such an issue.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a substantial number of the non-Mediterranean variant was unexpected, and perhaps related to the more heterogeneous background of the Iraqi people. With respect to ethnicity, 6% of Arabs, 8.8% of Kurds, and 5.6% of Turkomans were G6PD-deficient [22].…”
Section: Epidemiology Of G6pd Deficiency In Arab Countries: Key Findingsmentioning
confidence: 97%